Exploring the Characteristics and Utilization of General Practice Healthcare by Adults With Cerebral Palsy: A Systematic Review - Prue Morgan; Asfarina Zanudin (Journal of Primary Care & Community Health)
Background: Individuals with cerebral palsy (CP) experience acute and chronic health issues requiring lifespan primary care. This review aimed to investigate characteristics and utilization of general practitioner (GP) access by adults with CP. Secondary aims included exploring reasons prompting access, identifying interventions provided, and personal features affecting access. Methods: Using systematic review methodology, 5 databases were searched using keywords relating to adults, CP, and primary care, relating to quantitative studies (January 2000-July 2024). Data was extracted, collated, and analyzed descriptively, with additional meta-analyses to estimate proportion of GP visits. Results: Fifteen studies were included describing GP access by 6231 adults with CP. The proportion annually accessing a GP was 78% (95% CI = 69%-85%). The frequency of GP access ranged from 1.76 to 11.7 visits per year, increased with advancing age and disability severity. Comorbid intellectual disability and pain also increased GP attendance. Limited data was available reporting healthcare needs prompting GP access, and no interventions were described. Conclusions: Advancing age, greater disability severity, comorbid intellectual disability, and pain may prompt increased GP access by adults with CP. Identification of reasons for seeking primary care, and interventions provided are required through data linkage studies to enhance lifespan care.